Wars and heroes: the romantic representation of Spain in "Don Juan; or the Battle of Tolosa" (1816) - Medina Calzada, Sara (Journal of English Studies, 2017)
This paper examines “Don Juan; or the Battle of Tolosa”, an anonymous poem published inLondonin 1816. This metrical tale set in medievalIberiaat the time of the so-called “reconquista” recreates the Battle of Las Navas de Tolosa (1212), in which the Muslim forces were defeated by a Christian coalition near Sierra Morena. The poet clearly sides with the Christians, who are depicted as brave warriors struggling to recover their land and their freedom. The emphasis on their patriotic heroism against foreign usurpation creates an implicit analogy between the medieval battle and the recent events of the Peninsular War (1808-1814). The representation ofSpainas a land of war and romance echoes the Romantic figurations of this country appearing in British print culture in the early nineteenth century.